PENINGKATAN PROFIL PELAJAR PANCASILA PESERTA DIDIK DALAM MATERI MAKRAME MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) DI KELAS V SDN 01 LADANG CAKIAH KOTA BUKITTINGGI - Aprilia, Cynthia; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low level of application of the Pancasila Student Profile dimensions of students in learning macrame material because the learning process is still teacher-centered, so that students are less actively involved in the learning process. This research aims to describe how to improve the Pancasila Student Profile of students in macrame material using the Project Based Learning (PjBL) model in class V of SDN 01 Ladang Cakiah, Bukittinggi City.This type of research is Classroom Action Research (PTK) with a qualitative approach and a quantitative approach. This research was carried out in 2 cycles with research procedures consisting of 4 stages, namely: planning, implementation, observation and reflection. The data in this research consists of qualitative data and quantitative data with the data source being the process of learning macrame material using the Project Based Learning (PjBL) model. Data collection techniques used in this research were tests and non-tests. The instruments used are test and non-test sheets. The subjects in this research were class teachers as observers, researchers as practitioners and 29 students consisting of 12 male students and 17 female students.The research results showed that: First, the teaching module for cycle I, meeting I, obtained an average of 79.16% (B), cycle I, meeting II, 87.5% (A), then increased in cycle II to 95.83% (A). . Second, the results of the teacher's learning aspects in cycle I, meeting I, obtained an average of 78.12% (B), cycle I, meeting II 90.62% (A), then increased in cycle II to 96.87% (A). Third, the results of the implementation of learning aspects for students in cycle I, meeting I, obtained an average of 75%, cycle I, meeting II, 87.5% (A), then increased in cycle II to 93.75% (A). Fourth, the results of the Pancasila Student Profile assessment for cycle I, meeting I, obtained an average of 71 (B), cycle I, meeting II 82.64 (A), then increased in cycle II to 89.11 (A). The five learning outcomes for cycle I, meeting I, obtained an average of 77.07 (B), cycle I, meeting II, obtained an average of 83.08 (A), then increased in cycle II to 92.63 (A). Thus, it can be concluded that the Project Based Learning (PjBL) model can improve the Pancasila Student profile of students in macrame material in class V of SDN 01 Ladang Cakiah, Bukittinggi City. Keywords: Pancasila Student Profile, Macrame, Project Based Learning (PjBL)